Growth instability and surface phase transition of Ti thin film on Si(1 1 1): An atomic force microscopy study - Aurongzeb, Deeder (Applied surface science, 2006)
Evolution of surface structure during the annealing of e-beam evaporated Ti films is studied by means of atomic force microscopy (AFM). Image variography and power spectral density analysis are used to study scaling properties of the films, ranging from 50 nm to 20 μm length scale. No particular grain size is observed up to 473 K. At 673 K, grain size of ∼250 nm are formed and coalesced to form bigger grain size upon further annealing. At 473 K, RMS roughness dropped at all length scale and became rougher at 673 K with an increasing trend up to 873 K. Clustering at 673 K indicates Kosterlitz–Thaouless [J.M. Kosterlitz, D.J. Thaouless, J. Phys. Chem. 6 (1973) 1181] type phase transition at the surface. The observed transition is also consistent with existing scaling laws.